Gymnastic Sports Management Training for Physical Education Teachers in East Jakarta City - Herman Chaniago; Wahyuningtyas Puspitorini; Yafi Velyan Mahyudi (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2024)
In the gymnastics sports event (O2SN), students will have greater opportunities to take part in the event. For this reason, the competence of physical education teachers must be improved through training and knowledge about teaching basic gymnastic movements. However, physical education teachers in East Jakarta lack gymnastics management training, but do not understand sports coaching techniques and management. The service methods used in this activity are training, seminars and workshops. This service was carried out for approximately 2 months with the following stages: 1) conducting training, 2) monitoring, 3) evaluating and achieving. Participants involved in the service program are 35 physical education teachers in the East Jakarta region. Program implementation involves the implementation of a previously designed sports curriculum. This includes organizing the lesson schedule, selecting teaching methods appropriate to the type of sport, as well as managing groups of participants. Factors such as safety, health, and ethics must also be considered in implementing physical education programs. Supervision and monitoring are carried out to ensure that the sports program runs according to plan. Community service with the topic